Sudut Elevasi dan MUF pada Sistem Komunikasi Radio HF Lintasan Merauke - Surabaya - Indah Kurniawati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
HF radio which frequency allocations 3-30 MHz is suitable for communication in long distance, wide, separated by oceans and remote area. This system is to be an alternative for a high cost satellite technology, especially Indonesian area where there is no communication system there. In this paper, we discussed long distance HF communication system parameters, namely elevation angle and Maximum Usable Frequency for Merauke-Surabaya link. For computation, the radius of the earth used was radius of the earth in equator. Ionosphere variation conditions were obtained from ionosonde measurement operated in Kupang by LAPAN in March 2013. The results of this computation are : if HF radio waves are reflected once, the elevation angle will be too small so that it was difficult to apply for antenna. In order to make it simple to apply, radio waves has to be reflected twice in F layer. The other result are that MUF values depend on foF2 variations for each days where MUF is higher in a day than in a night.